LANGUAGE AND STYLE OF NUŠIĆ’S COLUMNS - Spasic, Jelena Lj. (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2019)
The paper aims to determine the repertoire of linguistic and stylistic means in Nušić’s columns published in daily newspaper Politika. The primary methods used in this paper were functional-stylistic and linguistic-stylistic ones. We have shown that Nušić’s text published in the Politika have the linguistic and stylistic characteristics of column, but also have some individual characteristics of Nušić’s style. The analysis was conducted by separating elements of belletristic functional style and elements of colloquial functional style in Nušić’s newspaper columns. The analysis of Nušić’s choices of linguistic means for attracting attention and achieving humorous effect was conducted in order to argue the claim that Branislav Nušić was the forerunner of Serbian columnist. The stylistic analysis also points to the importance of Nušić’s journalistic work for the development of modern Serbian journalism. The research is a contribution to journalism stylistics and also contributes to the study of linguistic-stylistic characteristics of non-literary texts.
Keywords: newspapers; journalism stylistics; stylistics; column; Politika; Branislav Nušić